Positive electrode material, preparation method thereof and lithium ion battery

By using composite clad materials on lithium-rich manganese-based materials, using three-dimensional mesh structures formed by carbon elements and lithium vanadate and other materials, the instability problem caused by the interfacial reaction of the material during charge and discharge is solved, and the electrochemical performance and cyclic stability are significantly improved.

CN119812280AActive Publication Date: 2025-04-11CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510036943.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The interface reaction between the lithium-rich manganese-based material and the electrolyte during charging and discharge leads to instability of the material's crystal structure, irreversible oxygen loss and transition metal migration, resulting in attenuation of the material's cycling process voltage and capacity, low first-time Coulomb efficiency and poor cycling stability.

Method used

The composite coating material is used to coat lithium-rich manganese-based materials. The composite coating material consists of a three-dimensional network structure formed by carbon elements and other materials such as lithium vanadate. It prevents high-valent metal cations from reacting with reactive oxygen species through physical barriers, and restricts the reactive oxygen species generated by charging to the inside of the material.

Benefits of technology

The first Coulomb efficiency, cycle stability and rate performance of the positive electrode material are improved, oxygen loss and side reactions are reduced, and the overall structural stability and electrochemical performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812280A_ABST
    Figure CN119812280A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries. The positive electrode material comprises a core material and a composite coating material. And the core material comprises a lithium-rich manganese-based material. The outer surface of the core material is coated with the composite coating material. The composite coating material comprises a first material and a second material, the first material comprises a carbon element, and the first material forms a three-dimensional network structure with a cavity; the second material comprises a part located on the outer surface of the three-dimensional net-shaped structure and further comprises a part located in a cavity of the three-dimensional net-shaped structure; the second material is at least used for realizing a lithium storage function. Therefore, the technical problem of relatively poor interface stability of the positive electrode and the electrolyte in the prior art can be at least solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the vigorous development of electric vehicles, energy storage technology industries and portable electronic products, the demand for high energy density electrode materials is growing, which has greatly promoted the development of electrode materials. Among the many positive electrode materials, lithium-rich manganese-based materials are regarded as the most promising positive electrode materials for the next generation of lithium-ion batteries due to their ultra-high specific capacity, high energy density, high voltage characteristics and significant cost advantages.

[0003] However, the interfacial reaction between lithium-rich manganese-based materials and the electrolyte during the charging and discharging process will cause problems such as unstable crystal structure, irreversible oxygen loss and transition metal migration of lithium-rich manganese-based materials, leading to voltage and capacity decay during the material cycle process, low first coulombic efficiency and poor cycle stability, which seriously restricts its commercial application. Summary of the invention

[0004] The present application provides a positive electrode material and a preparation method thereof, and a lithium-ion battery, to at least solve the technical problem of poor interface stability between the positive electrode and the electrolyte in the related art. In order to achieve the above purpose, the technical solution adopted in the present application is as follows:

[0005] According to the first aspect of the present application, a positive electrode material is provided; the positive electrode material comprises: a core material and a composite coating material. The core material comprises a lithium-rich manganese-based material. The composite coating material is coated on the outer surface of the core material. The composite coating material comprises a first material and a second material, the first material comprises a carbon element, and the first material forms a three-dimensional network structure with a cavity; the second material comprises a portion located on the outer surface of the three-dimensional network structure, and also comprises a portion located in the cavity of the three-dimensional network structure; the second material is at least used to realize the lithium storage function.

[0006] According to the above technical means, the composite coating material can form a coating layer on the outer surface of the core material. The coating layer can physically block the positive electrode material and the electrolyte, prevent the high-valent metal cations and active oxygen species on the surface of the core material from reacting with the electrolyte, and inhibit the corrosion of HF in the electrolyte. In addition, the composite coating material can also confine the active oxygen species generated by charging to the interior of the core material to prevent oxygen escape. Moreover, in the above-mentioned composite coating material, the first material can be interwoven to form a three-dimensional network structure, so that the second material can be arranged on the outer surface of the three-dimensional network structure and inside the cavity of the three-dimensional network structure, so that the second material has a larger spacing inside, which can provide an effective channel for lithium ion embedding / ejection, and reduce the charge transfer impedance of lithium ions between the positive electrode material particles, which is beneficial to Li +The efficient shuttle of the positive electrode material can improve the electrochemical performance of the battery cell, such as the first coulombic efficiency, cycle stability, and rate. In addition, the first material includes carbon elements, which makes the positive electrode material have better electrochemical performance.

[0007] In a possible implementation, the first material includes at least one of carbon nanotubes, graphene, and porous carbon.

[0008] According to the above technical means, the first material will not collapse after multiple charge and discharge cycles, which can improve the structural stability of the composite coating material.

[0009] In one possible implementation, the first material includes multi-walled carbon nanotubes.

[0010] According to the above technical means, multi-walled carbon nanotubes have the advantages of high strength, high toughness, good conductivity and durability, so that the electrochemical performance of the positive electrode material can be improved, and the structural stability of the composite coating material can be improved. In addition, multi-walled carbon nanotubes have a large specific surface area, which is conducive to the adsorption of the second material on the three-dimensional network structure.

[0011] In one possible implementation, the second material includes lithium vanadate (LiV3O8).

[0012] According to the above technical means, lithium vanadate (LiV3O8) has a layered structure, which can form more space for storing lithium ions and reduce the irreversible insertion and extraction of lithium ions. Moreover, when lithium vanadate (LiV3O8) includes a part located on the outer surface of the three-dimensional network structure and a part located in the cavity of the three-dimensional network structure, the second material can have a larger interlayer spacing in structure, providing an effective channel for lithium ion insertion / extraction, which is beneficial to Li + The efficient shuttling of the cells can improve the electrochemical performance of the cells, such as the first coulombic efficiency, cycle stability, and rate.

[0013] In a possible implementation manner, the thickness of the composite coating material is in the range of 15 nm to 30 nm.

[0014] According to the above technical means, the thickness of the composite coating material is relatively large, which can enhance the physical barrier effect of the composite coating material, prevent oxygen escape, inhibit the corrosion of HF in the electrolyte, etc., and can solve the problems of low initial coulombic efficiency, poor rate performance and cycle stability of the positive electrode material.

[0015] In a possible implementation, in the composite coating material, the mass ratio of the first material to the second material is in the range of (0.02-0.03):1.

[0016] According to the above technical means, the three-dimensional network structure formed by the first material can provide sufficient accommodation space for the second material, thereby improving the structural stability of the composite coating material.

[0017] In a possible implementation, the core material includes: a core material and a doping material, wherein the doping material covers the core material; the doping material includes: a lithium-rich manganese-based material containing tungsten ions.

[0018] According to the above technical means, the doping material can form a coating core material and is rich in tungsten ions (W 6+ ) doping layer. The introduction of tungsten can improve the overall structural stability and thermal stability of the positive electrode material, increase the cycle life, and improve the electrochemical properties of the battery cell such as cycle stability and rate.

[0019] In one possible implementation, the atomic percentage of tungsten ions in the core material is in the range of 2% to 3%.

[0020] According to the above technical means, the tungsten ion (W 6+ ) Improve the stability of the crystal structure of lithium-rich manganese-based materials (LRM), reduce the occurrence of side reactions, and accelerate Li + The effect of diffusion rate can further improve the electrochemical performance of the battery cell, such as cycle stability and rate.

[0021] In a possible implementation, the core material further includes nickel and cobalt; the atomic percentage of nickel in the core material is less than the atomic percentage of manganese in the core material, and greater than the atomic percentage of cobalt in the core material.

[0022] According to the above technical means, the core material includes lithium manganese nickel cobalt compound, which makes the core material have high energy density, long life, high safety, low cost and good cycle performance.

[0023] According to the second aspect provided by the present application, a method for preparing a positive electrode material is provided. The preparation method comprises:

[0024] A core material is formed, the core material comprising a lithium-rich manganese-based material.

[0025] A composite coating material is formed and coated on the outer surface of the core material; the composite coating material includes a first material and a second material, the first material includes carbon elements, and the first material forms a three-dimensional network structure with a cavity; the second material includes a portion located on the outer surface of the three-dimensional network structure, and also includes a portion located in the cavity of the three-dimensional network structure; the second material is at least used to realize the lithium storage function.

[0026] It should be noted that the technical effects brought about by the second aspect can refer to the technical effects brought about by the corresponding implementation method in the first aspect, and will not be repeated here.

[0027] In a possible implementation, forming the core material includes: mixing a first lithium source, a manganese source, and a tungsten source to obtain a mixed powder; and calcining the mixed powder to obtain the core material.

[0028] In one possible embodiment, the manganese source is selected from any one of the following general formulas as shown in the structure: Ni b Co c Mn 1-b-c (OH)2; where 0≤c≤0.05, 0 <b≤0.4。

[0029] According to the above technical means, the core material is synthesized by a high temperature solid phase method. On the one hand, the core material can include lithium manganese nickel cobalt compound or lithium manganese nickel compound, so that the core material has high energy density, long life, high safety, low cost and good cycle performance. On the other hand, it can form a core material coated with tungsten ions (W 6+ ) doping layer, the introduction of W element can improve the overall structural stability and thermal stability of the positive electrode material.

[0030] In a possible implementation, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; and / or the tungsten source includes at least one of tungsten trioxide, tungsten sulfide and tungsten carbide.

[0031] In a possible implementation manner, the calcination temperature of the mixed powder is in the range of 600° C. to 800° C.; and / or the calcination time of the mixed powder is in the range of 6 h to 8 h.

[0032] In a possible implementation, the second material includes lithium vanadate, and a reaction for forming the second material is a solvothermal reaction.

[0033] According to the above technical means, on the one hand, the layered structure of lithium vanadate (LiV3O8) can be used to increase the space for storing lithium ions and reduce the irreversible deintercalation of lithium ions. Moreover, the second material can have a larger interlayer spacing in structure, providing an effective channel for lithium ion insertion / extraction. On the other hand, the distribution of the formed second material can be made more uniform, and the second material can be more evenly distributed on the outer surface of the three-dimensional network structure formed by the first material, and in the cavity of the three-dimensional network structure, which can reduce the charge transfer impedance of lithium ions between the positive electrode material particles, which is beneficial to Li + The efficient shuttling of the cells can improve the electrochemical performance of the cells, such as the first coulombic efficiency, cycle stability, and rate.

[0034] In one possible implementation, the reaction temperature of the solvothermal reaction for forming the second material is in the range of 60°C to 80°C.

[0035] In one possible embodiment, a composite coating material is formed and coated on the outer surface of a core material, comprising: subjecting a vanadium source and a second lithium source to a first stage of a solvothermal reaction to obtain a first solution; wherein the configuration ratio of vanadium in the vanadium source to lithium in the second lithium source is 3:1, and the first solution comprises lithium vanadate; adding a carbon source to the first solution to a second stage of a solvothermal reaction to obtain a second solution; adding the core material to the second solution to a third stage of a solvothermal reaction to obtain a first precipitate; and calcining the first precipitate to obtain the positive electrode material.

[0036] According to the above technical means, the lithium vanadate (LiV3O8) formed in the first stage of the solvothermal reaction can enter the cavity of the three-dimensional network structure formed by the first material. In the second stage of the solvothermal reaction, lithium vanadate (LiV3O8) can be in situ formed in the cavity and outer surface of the three-dimensional network structure formed by the first material, and the composite coating material can be densely coated on the surface of the core material. In this way, the electronic conductivity and ionic conductivity of the positive electrode material can be improved, and the storage space of lithium ions can be enhanced to reduce Li + The irreversible deintercalation of lithium ions improves the overall electrochemical performance; thirdly, it can provide an effective channel for lithium ion insertion / extraction, which is beneficial to Li + In addition, in the third stage of the solvothermal reaction, lithium vanadate (LiV3O8) can be in-situ formed on the outer surface of the core material, which can further improve the electrochemical performance of the battery cell, such as the first coulombic efficiency, cycle stability, and rate.

[0037] In one possible embodiment, the reaction time of the first stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction; and / or, the reaction time of the third stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction.

[0038] In one possible embodiment, the reaction time of the first stage of the solvothermal reaction ranges from 1h to 2h; and / or, the reaction time of the second stage of the solvothermal reaction ranges from 0.2h to 1h; and / or, the reaction time of the third stage of the solvothermal reaction ranges from 1h to 2h.

[0039] According to the above technical means, firstly, the amount of lithium vanadate (LiV3O8) formed in the first stage of the solvothermal reaction can be increased, which is conducive to the lithium vanadate (LiV3O8) entering the cavity of the three-dimensional network structure formed by the first material. Secondly, the reaction sufficiency of in-situ formation of lithium vanadate (LiV3O8) in the cavity and outer surface of the three-dimensional network structure in the second stage of the solvothermal reaction can be improved. Thirdly, the reaction sufficiency of in-situ formation of lithium vanadate (LiV3O8) on the outer surface of the core material in the third stage of the solvothermal reaction can be improved.

[0040] In one possible implementation, the carbon source includes at least one of carbon nanotubes, graphene, and porous carbon.

[0041] In one possible embodiment, the carbon source includes acid-treated multi-walled carbon nanotubes.

[0042] According to the above technical means, a plurality of active sites can be formed on the surface of multi-walled carbon nanotubes. These active sites can be used to connect the second material, which can increase the connection reliability between the first material and the second material, and can increase the adsorption amount of the second material on the three-dimensional network structure formed by the first material, thereby forming more space for storing lithium ions and reducing the irreversible deintercalation of lithium ions.

[0043] In a possible implementation, the carbon source is multi-walled carbon nanotubes treated with concentrated sulfuric acid and / or concentrated nitric acid; the acid treatment process is ultrasonic treatment; and the acid treatment time ranges from 2 h to 4 h.

[0044] According to the above technical means, the acid treatment degree of the multi-walled carbon nanotubes can be improved, and more active sites can be formed on the multi-walled carbon nanotubes.

[0045] In one possible embodiment, the vanadium source includes ammonium vanadate; and / or, the second lithium source includes lithium hydroxide monohydrate.

[0046] In a possible implementation, the calcination temperature of the first precipitate is in the range of 350° C. to 400° C.; and / or the calcination time of the first precipitate is in the range of 10 h to 12 h.

[0047] According to a third aspect provided by the present application, a lithium-ion battery is provided, comprising the positive electrode material of any one of the possible implementation modes described above, or the positive electrode material prepared by the preparation method of any one of the possible implementation modes described above.

[0048] It should be noted that the technical effects brought about by the third aspect can be referred to the technical effects brought about by the corresponding implementation method in the first aspect, and will not be repeated here.

[0049] Beneficial effects of this application:

[0050] (1) The positive electrode material in the present application includes a composite coating material. The composite coating material can form a coating layer on the outer surface of the core material. The coating layer can physically block the positive electrode material and the electrolyte, prevent the high-valent metal cations and active oxygen species on the surface of the core material from reacting with the electrolyte, and inhibit the corrosion of HF in the electrolyte. In addition, the composite coating material can also confine the active oxygen species generated by charging to the interior of the core material to prevent oxygen escape. Moreover, in the above-mentioned composite coating material, the first material can be interwoven to form a three-dimensional network structure, so that the second material can be arranged on the outer surface of the three-dimensional network structure and in the cavity of the three-dimensional network structure, so that the second material has a larger spacing inside, which can provide an effective channel for lithium ion embedding / ejection, reduce the charge transfer impedance of lithium ions between the positive electrode material particles, and is beneficial to Li + The efficient shuttling of the positive electrode material improves the first coulombic efficiency, high voltage, high rate or high cycle electrochemical performance of the positive electrode material, thereby improving the first coulombic efficiency, cycle stability, rate and other electrochemical performance of the battery cell. In addition, the first material includes carbon elements, which makes the positive electrode material have better electrochemical performance.

[0051] (2) In the case where the core material includes a core material and a doping material, the doping material can form a coating on the core material and is rich in tungsten ions (W 6+ ) doping layer. The introduction of tungsten can improve the overall structural stability and thermal stability of the positive electrode material, increase the cycle life, and improve the electrochemical properties of the battery cell such as cycle stability and rate.

[0052] (3) In the preparation method of the positive electrode material in the present application, the reaction to form the second material can be a solvothermal reaction, and the solvothermal reaction can be carried out in at least three stages, wherein the lithium vanadate (LiV3O8) formed in the first stage of the solvothermal reaction can enter the cavity of the three-dimensional network structure formed by the first material, and in the second stage of the solvothermal reaction, lithium vanadate (LiV3O8) can be formed in situ inside the cavity and on the outer surface of the three-dimensional network structure formed by the first material, and the composite coating material is densely coated on the surface of the core material, so that the electronic conductivity and ionic conductivity of the positive electrode material can be improved, and the storage space of lithium ions can be enhanced, thereby reducing Li + Irreversible deintercalation and insertion improves the overall electrochemical performance; it can also provide an effective channel for lithium ion insertion / extraction, which is beneficial to Li + The efficient shuttling of the cells can improve the electrochemical performance of the cells, such as the first coulombic efficiency, cycle stability, and rate.

[0053] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1is a schematic structural diagram of a positive electrode material according to an exemplary embodiment;

[0055] Figure 2 yes Figure 1 A partial enlarged view of the middle A;

[0056] Figure 3 is a graph showing a rate cycle test result of a lithium-ion battery according to an exemplary embodiment;

[0057] Figure 4 The figure is a diagram showing the result of the first charge and discharge test of a lithium-ion battery according to an exemplary embodiment.

[0058] Among them, 100 is positive electrode material; 10 is core material; 11 is core material; 12 is doping material; 20 is composite coating material; 21 is first material; 22 is second material. DETAILED DESCRIPTION

[0059] The following will describe the implementation methods of the present application with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be understood that the preferred embodiments are only for illustrating the present application, not for limiting the scope of protection of the present application.

[0060] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present application, and thus the drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed at will, and the component layout may also be more complicated.

[0061] Some embodiments of the present application provide a lithium-ion battery. The lithium-ion battery, for example, includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrolyte includes lithium ions.

[0062] Based on the above structure, during the battery charging and discharging process, lithium ions can be inserted and removed back and forth between the positive electrode and the negative electrode. The electrolyte can play the role of conducting lithium ions. The separator allows lithium ions to pass through and prevents the positive and negative electrodes from short-circuiting.

[0063] Exemplarily, the positive electrode plate includes a first current collector and a positive electrode film layer disposed on at least one surface of the first current collector, wherein the positive electrode film layer includes a positive electrode material.

[0064] Exemplarily, the first current collector may be a metal foil, such as aluminum foil or copper foil; or, the first current collector may be a composite current collector, which may include a stacked base layer and a metal layer, wherein the base layer is a polymer material base layer.

[0065] Exemplarily, the positive electrode material may include at least one of a lithium-containing phosphate and a lithium transition metal oxide, wherein the lithium transition metal oxide includes, for example, at least one of lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium manganese nickel oxide, and lithium manganese nickel cobalt oxide.

[0066] Exemplarily, the negative electrode plate includes a second current collector and a negative electrode film layer disposed on at least one surface of the second current collector, and the negative electrode film layer includes a negative electrode material.

[0067] Here, the exemplary description of the second current collector can refer to the above description of the first current collector, which will not be repeated here. Moreover, the first current collector and the second current collector can be the same or different, which is not limited here.

[0068] Exemplarily, the negative electrode material may include at least one of soft carbon, hard carbon, graphite, silicon, silicon oxide, silicon alloy, tin, tin oxide, and tin alloy.

[0069] Exemplarily, the electrolyte includes an electrolyte salt and a solvent. The electrolyte salt includes, for example, at least one of lithium difluorophosphate, lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, and lithium tetrafluorooxalate phosphate. Of course, the electrolyte salt may also be other types of lithium electrolyte salts.

[0070] Among the above cathode materials, lithium-rich manganese-based materials (LRMs) are regarded as the most promising cathode materials for the next generation of lithium-ion batteries. With the advancement of technology and the improvement of the industrial chain, a variety of modification strategies have been proposed to improve the electrochemical performance of lithium-rich manganese-based cathodes.

[0071] In some embodiments, the lithium-rich manganese-based material is modified by surface modification, bulk doping, morphology and structure, etc. Through modification, the problems of lattice oxygen loss and metal ion migration during the cycle of the lithium-rich manganese-based material can be effectively alleviated, thereby improving the material's cycle performance and first coulomb efficiency and other properties.

[0072] In some implementations, a Na-doped cobalt-free lithium-rich manganese-based cathode material is prepared, and a Na-doped high-capacity cobalt-free lithium-rich manganese-based cathode material is prepared by a sol-gel method. Na is doped into the material lattice to expand the Li interlayer spacing and promote Li + It diffuses and acts as a "pillar" in the crystal lattice to avoid the collapse of the crystal structure, which can effectively improve the capacity and cycle stability of the material.

[0073] As mentioned in the background, how to improve the interfacial stability between the positive electrode and the electrolyte is the main challenge facing lithium-rich manganese-based positive electrode materials.

[0074] Based on this, some embodiments of the present application provide a positive electrode material 100, such as Figure 1 and Figure 2 As shown, the positive electrode material 100 includes: a core material 10 and a composite coating material 20. The core material 10 includes a lithium-rich manganese-based material. The composite coating material 20 is coated on the outer surface of the core material 10. The composite coating material 20 includes a first material 21 and a second material 22, the first material 21 includes a carbon element, and the first material 21 forms a three-dimensional network structure with a cavity; the second material 22 includes a portion located on the outer surface of the three-dimensional network structure, and also includes a portion located in the cavity of the three-dimensional network structure; the second material 22 is at least used to realize the lithium storage function.

[0075] Through the above arrangement, the surface coating of the core material 10 can be achieved, and the surface coating is an effective means to inhibit oxygen loss and surface side reactions. The above-mentioned composite coating material 20 can form a coating layer on the outer surface of the core material 10, and the coating layer can physically block the positive electrode material 100 and the electrolyte, prevent the high-valent metal cations and active oxygen species on the surface of the core material 10 from reacting with the electrolyte, and can also inhibit the corrosion of HF in the electrolyte. In addition, the composite coating material 20 can also limit the active oxygen species generated by charging to the inside of the core material 10, prevent oxygen from escaping, and thus alleviate the problems of low initial coulomb efficiency, poor rate performance and cycle stability of the positive electrode material 100.

[0076] Moreover, the composite coating material 20 includes a first material 21 and a second material 22. The first material 21 can be interwoven to form a three-dimensional network structure with cavities, so that the second material 22 can be arranged on the outer surface and inside of the three-dimensional network structure, so that the first material 21 and the second material 22 (for example, in the form of particles) can be composited, and the second material 22 has a larger spacing inside, which can provide an effective channel for lithium ion insertion / extraction, so that the charge transfer impedance of lithium ions between the particles of the positive electrode material 100 becomes smaller, which is beneficial to Li + The efficient shuttle of the positive electrode 100 can improve the electrochemical performance of the battery cell, such as the first coulombic efficiency, cycle stability, and rate. In addition, the first material 21 includes carbon elements, so that the first material 21 has good electronic conductivity, and the positive electrode material 100 has good electrochemical performance.

[0077] In a possible implementation, the first material 21 includes at least one of carbon nanotubes, graphene, and porous carbon.

[0078] In some examples, the first material 21 includes carbon nanotubes, graphene, or porous carbon; in other examples, the first material 21 includes any combination of carbon nanotubes, graphene, and porous carbon.

[0079] When the first material 21 includes at least one of carbon nanotubes, graphene and porous carbon, the first material 21 will not collapse after multiple charge and discharge cycles. For example, when the first material 21 includes carbon nanotubes, the cylindrical structure formed by the first material 21 will not collapse. In this way, the structural stability of the composite coating material 20 can be improved.

[0080] In one possible implementation, the first material 21 includes multi-walled carbon nanotubes (MWCNTs).

[0081] Multi-walled carbon nanotubes have the advantages of high strength, high toughness, good conductivity and durability, so that the electrochemical performance of the positive electrode material 100 can be improved, and the structural stability of the composite coating material 20 can be improved. In addition, multi-walled carbon nanotubes have a large specific surface area, which is conducive to the adsorption of the second material 22 on the three-dimensional network structure.

[0082] In one possible implementation, the second material 22 includes lithium vanadate (LiV3O8).

[0083] Lithium vanadate (LiV3O8) has a layered structure and a lithium embedding structure, which can form more space for storing lithium ions and reduce the irreversible embedding and de-embedding of lithium ions. Moreover, when the second material 22 includes lithium vanadate (LiV3O8), and the second material 22 includes a portion located on the outer surface of the three-dimensional network structure and a portion located in the cavity of the three-dimensional network structure, the second material 22 can have a larger interlayer spacing in structure, providing an effective channel for the embedding / de-embedding of lithium ions. In this way, the charge transfer impedance of lithium ions between the particles of the positive electrode material 100 can be reduced, which is beneficial to the Li + The efficient shuttling of the cells can improve the electrochemical performance of the cells, such as the first coulombic efficiency, cycle stability, and rate.

[0084] In a possible implementation manner, the thickness of the composite coating material 20 is in the range of 15 nm to 30 nm.

[0085] Exemplarily, the thickness of the composite coating material 20 is 15 nm, 18 nm, 21 nm, 24 nm, 27 nm or 30 nm, etc., which is not limited here.

[0086] When the thickness range of the composite coating material 20 is 15nm to 30nm, the thickness of the composite coating material 20 is relatively large, which can enhance the physical barrier effect of the composite coating material 20, prevent oxygen escape, inhibit the corrosion of HF in the electrolyte, etc., and can solve the problems of low initial coulombic efficiency of the positive electrode material 100, poor rate performance and cycle stability.

[0087] In a possible implementation, in the composite coating material 20, the mass ratio of the first material 21 to the second material 22 is in the range of (0.02-0.03):1.

[0088] Illustratively, in the composite coating material 20 , the mass ratio of the first material 21 to the second material 22 may be 0.02:1, 0.023:1, 0.025:1, 0.028:1 or 0.03:1, etc., which is not limited here.

[0089] Through the above-mentioned arrangement, the mass ratio of the first material 21 to the second material 22 in the composite coating material 20 can be within an appropriate range, so that the three-dimensional network structure formed by the first material 21 can provide sufficient accommodation space for the second material 22, thereby improving the structural stability of the composite coating material 20.

[0090] In a possible implementation, Figure 1 and Figure 2 As shown, the core material 10 includes: a core material 11 and a doping material 12, wherein the doping material 12 covers the core material 11; the doping material 12 includes: a tungsten ion (W 6+ )'s lithium-rich manganese-based materials.

[0091] It can be understood that the tungsten ion (W 6+ ) can form a doping material 12 that covers the core material 11 and is rich in tungsten ions (W 6+ ) doping layer. The introduction of W element can improve the overall structural stability and thermal stability of the positive electrode material 100, increase the cycle life, and improve the electrochemical performance of the battery cell such as cycle stability and rate. 6+ ) can enter the crystal lattice of lithium-rich manganese-based materials (LRM) and have a strong bonding force with oxygen, which can improve the stability of the crystal structure of lithium-rich manganese-based materials (LRM). 6+ ) is a high-valence W element ion. When the core material 10 includes nickel, the tungsten ion (W 6+ ) can induce low-valent Ni 2+The formation of W can induce the formation of rock salt or spinel structure on the surface, inhibit the release of lattice oxygen on the surface of the material, and prevent the transformation of the structure from layered to rock salt phase during the cycle, which can effectively reduce the occurrence of side reactions and effectively improve the structural stability and cycle life of layered lithium-rich manganese-based materials (LRM). Thirdly, W doping can expand the lattice parameters and form a high ion conductive layer, which can effectively reduce the lithium diffusion resistance and electron migration resistance, improve the diffusion kinetics of lithium, and accelerate Li + The diffusion rate of the battery can be increased, thereby improving the electrochemical performance of the battery cell, such as cycle stability and rate capability.

[0092] In one possible embodiment, tungsten ions (W 6+ ) in the core material 10 has an atomic percentage in the range of 2% to 3%.

[0093] For example, tungsten ions (W 6+ ) in the core material 10 has an atomic percentage of 2%, 2.3%, 2.5%, 2.7% or 3%, etc., which is not limited here.

[0094] Based on the above settings, tungsten ions (W 6+ ) in the core material 10 has a large atomic percentage, which can increase the tungsten ion (W 6+ ) Improve the stability of the crystal structure of lithium-rich manganese-based materials (LRM), reduce the occurrence of side reactions, and accelerate Li + The effect of diffusion rate can further improve the electrochemical performance of the battery cell, such as cycle stability and rate.

[0095] In one possible embodiment, the core material 10 also includes nickel (Ni) and cobalt (Co); the atomic percentage of nickel (Ni) in the core material 10 is less than the atomic percentage of manganese (Mn) in the core material 10, and greater than the atomic percentage of cobalt (Co) in the core material 10.

[0096] By such arrangement, the core material 10 includes a lithium manganese nickel cobalt compound, so that the core material 10 has high energy density, long life, high safety, low cost and good cycle performance.

[0097] In a second aspect, some embodiments of the present disclosure further provide a method for preparing a positive electrode material 100. The preparation method includes S1-S2.

[0098] S1: forming a core material 10, wherein the core material 10 includes a lithium-rich manganese-based material.

[0099] S2: Form a composite coating material 20 and coat the outer surface of the core material 10 with the composite coating material 20. The composite coating material 20 includes a first material 21 and a second material 22. The first material 21 includes carbon elements and forms a three-dimensional network structure with cavities; the second material 22 includes a part located on the outer surface of the three-dimensional network structure and also includes a part located in the cavities of the three-dimensional network structure; the second material 22 is at least used to achieve the function of lithium storage.

[0100] It should be noted that for the technical effects brought by the second aspect, reference can be made to the technical effects brought by the corresponding implementation manners in the first aspect, which will not be elaborated here.

[0101] In a possible implementation manner, forming the core material 10 includes S1.1 to S1.2.

[0102] S1.1: Mix a first lithium source, a manganese source, and a tungsten source to obtain a mixed powder.

[0103] In some embodiments, the manganese source is selected from any one of the structures represented by the following general formula: Ni b Co c Mn 1-b-c (OH)2; where 0 ≤ c ≤ 0.05 and 0 < b ≤ 0.4. For example, when c = 0.04 and b = 0.3, the manganese source is Ni 0.3 Co 0.04 Mn 0.66 (OH)2. The above manganese source can also be referred to as a manganese-based ternary hydroxide precursor.

[0104] Exemplarily, in the general formula Ni b Co c Mn 1-b-c (OH)2, the value of c can be 0, 0.01, 0.02, 0.03, 0.04, or 0.05, etc., and there is no limitation here.

[0105] Exemplarily, in the general formula Ni b Co c Mn 1-b-c (OH)2, the value of b can be 0.05, 0.1, 0.3, 0.3, or 0.4, etc., and there is no limitation here.

[0106] In some embodiments, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate.

[0107] In some embodiments, the tungsten source includes at least one of tungsten trioxide, tungsten sulfide, and tungsten carbide.

[0108] In some embodiments, the process of mixing the first lithium source, the manganese source, and the tungsten source is a ball milling process.

[0109] Illustratively, the rotation speed range of the ball milling process may be 300 r / min to 500 r / min, such as 300 r / min, 350 r / min, 400 r / min, 450 r / min or 500 r / min, etc., which is not limited here.

[0110] Exemplarily, the time for ball-milling the first lithium source, the manganese source and the tungsten source can be 1 h to 2 h, such as 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, etc., which is not limited here.

[0111] S1.2: calcining the mixed powder to obtain the core material 10.

[0112] In some embodiments, the calcination temperature of the mixed powder is in the range of 600°C to 800°C.

[0113] For example, the calcination temperature of the mixed powder may be 600° C., 650° C., 700° C., 750° C., or 800° C., etc., which is not limited herein.

[0114] In some embodiments, the calcination time of the mixed powder is in the range of 6 h to 8 h.

[0115] For example, the calcination time of the mixed powder can be 6 h, 6.5 h, 7 h, 7.5 h or 8 h, etc., which is not limited here.

[0116] It can be understood that, through the above-mentioned setting, the core material 10 is synthesized by a high temperature solid phase method. On the one hand, the core material 10 can include a lithium manganese nickel cobalt compound or a lithium manganese nickel compound, so that the core material 10 has high energy density, long life, high safety, low cost and good cycle performance. On the other hand, it can form a coated core material 11 and rich in tungsten ions (W 6+ ) doping layer, thus, as mentioned above, the introduction of W element can improve the overall structural stability and thermal stability of the positive electrode material 100.

[0117] In a possible implementation, the second material 20 includes lithium vanadate (LiV3O8), and the reaction for forming the second material 20 is a solvothermal reaction.

[0118] Through the above arrangement, on the one hand, the layered structure of lithium vanadate (LiV3O8) can be utilized to increase the space for storing more lithium ions and reduce the irreversible insertion and extraction of lithium ions. Moreover, the second material 22 can have a larger interlayer spacing in structure, providing an effective channel for the insertion / extraction of lithium ions. On the other hand, when the second material 20 is formed by solvent thermal reaction, compared with the case where the second material 20 is formed by solid phase reaction, the distribution of the formed second material 20 can be made more uniform, and the second material 20 can be more evenly distributed on the outer surface of the three-dimensional network structure formed by the first material 21, and in the cavity of the three-dimensional network structure. In this way, the second material 22 can have a larger interlayer spacing in structure, providing an effective channel for the insertion / extraction of lithium ions. In this way, the charge transfer impedance of lithium ions between the particles of the positive electrode material 100 can be reduced, which is beneficial to Li + The efficient shuttling of the cells can improve the electrochemical performance of the cells, such as the first coulombic efficiency, cycle stability, and rate.

[0119] In a possible implementation, the reaction temperature of the solvothermal reaction for forming the second material 20 is in a range of 60° C. to 80° C.

[0120] For example, the reaction temperature of the solvothermal reaction for forming the second material 20 may be 60° C., 65° C., 70° C., 75° C., or 80° C., etc., which is not limited here.

[0121] In a possible implementation, a composite coating material 20 is formed and coated on the outer surface of the core material 10 , including S2.1 to S2.4.

[0122] S2.1: The vanadium source and the second lithium source are subjected to the first stage of solvent thermal reaction to obtain a first solution; wherein the configuration ratio of vanadium in the vanadium source to lithium in the second lithium source is 3:1, and the first solution includes lithium vanadate (LiV3O8).

[0123] Exemplarily, the solvent of the first solution is deionized water.

[0124] Exemplarily, the vanadium source includes ammonium vanadate (NH4VO3).

[0125] Exemplarily, the second lithium source includes lithium hydroxide monohydrate (LiOH·H 2 O).

[0126] S2.2: Adding a carbon source to the first solution to carry out a second stage of solvothermal reaction to obtain a second solution.

[0127] Exemplarily, the carbon source includes at least one of carbon nanotubes, graphene, and porous carbon.

[0128] Exemplarily, the ratio of the carbon source added in S2.2 to the second material 22 is (0.02-0.03):1, such as 0.02:1, 0.023:1, 0.025:1, 0.028:1 or 0.03:1, etc., which is not limited here.

[0129] S2.3: Adding the core material to the second solution to carry out the third stage of the solvothermal reaction to obtain a first precipitate.

[0130] Illustratively, in S2.1, S2.2 and S2.3, the solvothermal reaction is carried out in a water bath under magnetic stirring, and the stirring speed may range from 250 r / min to 300 r / min, for example, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min or 300 r / min, etc., but is not limited thereto.

[0131] S2.4: calcining the first precipitate to obtain the positive electrode material.

[0132] In some embodiments, the calcination temperature of the first precipitate ranges from 350°C to 400°C.

[0133] For example, the calcination temperature of the first precipitate may be 350° C., 360° C., 370° C., 380° C., 390° C. or 400° C., etc., which is not limited herein.

[0134] By configuring in this way, the influence of the calcination process on the first material can be avoided.

[0135] In some embodiments, the calcination time of the first precipitate is in the range of 10 h to 12 h.

[0136] For example, the calcination time of the first precipitate can be 10 h, 10.5 h, 11 h, 11.5 h or 12 h, etc., which is not limited here.

[0137] Based on the above steps, the lithium vanadate (LiV3O8) formed in S2.1 can enter the cavity of the three-dimensional network structure formed by the first material 21, and the lithium vanadate (LiV3O8) can be formed in situ in the cavity and outer surface of the three-dimensional network structure formed by the first material 21 in S2.2. For example, NH4VO3 and LiOH·H2O co-precipitate to generate LiV3O8 in situ in the cavity and outer surface of the three-dimensional network structure, so that the second material 22 includes a portion located on the outer surface of the three-dimensional network structure and a portion located in the cavity of the three-dimensional network structure, and the composite coating material 20 is densely coated on the surface of the core material 10. In this way, firstly, the electronic conductivity and ionic conductivity of the positive electrode material 100 can be improved, and secondly, the storage space of lithium ions can be enhanced to reduce Li +The irreversible deintercalation can improve the comprehensive electrochemical performance; thirdly, it can provide an effective channel for lithium ion insertion / extraction, which reduces the charge transfer impedance of lithium ions between the particles of the positive electrode material 100, which is beneficial to Li + In addition, in S2.3, lithium vanadate (LiV3O8) can be formed in situ on the outer surface of the core material 10, so that the electrochemical properties of the battery cell, such as the first coulombic efficiency, cycle stability, and rate, can be further improved.

[0138] In some embodiments, after S2.3 and before S2.4, S2.3A is also included.

[0139] S2.3A: Filter, wash and dry.

[0140] Exemplarily, the washing solvent is deionized water, and the washing times are 3 times.

[0141] Exemplarily, the drying is carried out in a vacuum oven. The drying time may be 8 to 12 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, etc., which is not limited here.

[0142] Exemplarily, the temperature of the vacuum oven may be 100° C. to 120° C., such as 100° C., 105° C., 110° C., 115° C. or 120° C., etc., which is not limited herein.

[0143] Based on the above configuration, the temperature of the vacuum oven is within a suitable range, which can prevent the structure of the composite coating material 20 from being adversely affected during the drying process.

[0144] In a possible implementation, the reaction time of the first stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction.

[0145] In a possible implementation, the reaction time of the third stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction.

[0146] In a possible implementation manner, the reaction time of the first stage of the solvothermal reaction ranges from 1 h to 2 h.

[0147] Illustratively, the reaction time of the first stage of the solvothermal reaction can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, etc., which is not limited here.

[0148] It can be understood that through the above settings, the reaction time of the first stage of the solvothermal reaction is within an appropriate range, which can increase the amount of lithium vanadate (LiV3O8) formed in S2.1, and is conducive to the entry of lithium vanadate (LiV3O8) into the cavity of the three-dimensional network structure formed by the first material 21.

[0149] In a possible implementation manner, the reaction time of the second stage of the solvothermal reaction ranges from 0.2 h to 1 h.

[0150] For example, the reaction time of the second stage of the solvothermal reaction can be 0.2 h, 0.4 h, 0.6 h, 0.8 h or 1 h, etc., which is not limited here.

[0151] Through the above arrangement, the reaction time of the second stage of the solvothermal reaction is within an appropriate range, which can improve the reaction sufficiency when lithium vanadate (LiV3O8) is formed in situ in the cavity and outer surface of the three-dimensional network structure in S2.2.

[0152] In a possible implementation manner, the reaction time of the third stage of the solvothermal reaction ranges from 1 h to 2 h.

[0153] Illustratively, the reaction time of the first stage of the solvothermal reaction can be 1 h, 1.2 h, 1.5 h, 1.6 h, 1.8 h or 2 h, etc., which is not limited here.

[0154] Through the above arrangement, the reaction time of the third stage of the solvothermal reaction is within an appropriate range, which can improve the reaction sufficiency when lithium vanadate (LiV3O8) is formed in situ on the outer surface of the core material 10 in S2.3.

[0155] In one possible embodiment, the carbon source includes acid-treated multi-walled carbon nanotubes.

[0156] When the carbon source includes acid-treated multi-walled carbon nanotubes, a plurality of active sites can be formed on the surface of the multi-walled carbon nanotubes. These active sites can be used to connect the second material 22. This can increase the connection reliability between the first material 21 and the second material 22 and increase the adsorption amount of the second material 22 on the three-dimensional network structure formed by the first material 21, thereby forming more space for storing lithium ions and reducing the irreversible deintercalation of lithium ions.

[0157] In a possible implementation, the carbon source is multi-walled carbon nanotubes treated with concentrated sulfuric acid and / or concentrated nitric acid; the acid treatment process is ultrasonic treatment; and the acid treatment time ranges from 2 h to 4 h.

[0158] Illustratively, the acid treatment time may be 2 h, 2.5 h, 3 h, 3.5 h, or 4 h, etc., which is not limited here.

[0159] Illustratively, the temperature of the acid treatment may be 25° C. to 30° C., for example, 25° C., 26° C., 27° C., 28° C., 29° C. or 30° C., etc., which is not limited here.

[0160] Through the above-mentioned setting, the acid treatment degree of the multi-walled carbon nanotubes can be improved, and more active sites can be formed on the multi-walled carbon nanotubes. In this way, the connection reliability between the first material 21 and the second material 22 can be increased, and more space for storing lithium ions can be formed, reducing the irreversible insertion and extraction of lithium ions.

[0161] The following are examples of positive electrode materials and lithium-ion batteries provided according to the present application, as well as comparative examples provided according to related technologies.

[0162] Example 1

[0163] In this embodiment, positive electrode material A is prepared, and the preparation method includes R1 to R6.

[0164] R1: Lithium carbonate, tungsten trioxide and manganese-based ternary hydroxide Ni 0.4 Co 0.05 Mn 0.55 (OH)2 was configured according to the following molar ratios: Li / (Ni+Co+Mn)=1.2:1, W / (Ni+Co+Mn+W)=0.05:1; and ball milled at a speed of 400r / min for 2h to obtain a mixed powder.

[0165] R2: The mixed powder obtained in R1 was calcined at 650°C for 7h in air atmosphere, cooled naturally, and then crushed and sieved to obtain a core material with W element doped on the surface.

[0166] R3: NH4VO3 and LiOH·H2O are prepared in the following molar ratio: V / Li=3 / 1.0; and NH4VO3 and LiOH·H2O are dissolved in deionized water under magnetic stirring (the ratio between the sum of the masses of NH4VO3 and LiOH·H2O and the mass of deionized water is 1:40), and reacted in a water bath at 65°C for 2h to obtain a first solution.

[0167] R4: Acid-pretreated multi-walled carbon nanotubes (MWCNTs) are prepared in a ratio of 2% of the mass m(MWCNTs) of the acid-pretreated multi-walled carbon nanotubes to the mass m(LiV3O8) of lithium vanadate, and the acid-pretreated multi-walled carbon nanotubes are added to the first solution, and the water bath reaction is continued for 0.5h to obtain a second solution.

[0168] R5: Add the core material with surface doped with W element prepared in R2 to the second solution, continue stirring the reaction for 1 hour, filter, wash with deionized water 3 times, and dry in a vacuum oven at 100°C for 8 hours to obtain the first precipitate.

[0169] R6: The first precipitate was calcined at 350°C for 10 hours in an air atmosphere to obtain a positive electrode material A, which is a lithium-rich manganese-based positive electrode material doped with W element and modified by coating with a LiV3O8-MWCNTs composite material.

[0170] Example 2

[0171] Based on the positive electrode material A prepared in Example 1, a lithium ion button half-cell A was prepared.

[0172] Example 3

[0173] In this embodiment, positive electrode material B is prepared. The preparation method is similar to the preparation method in embodiment 1, and the only difference is that R1 is replaced by R1' as described below.

[0174] R1': Lithium carbonate and manganese-based ternary hydroxide Ni 0.4 Co 0.05 Mn 0.55 (OH)2 was prepared according to the following molar ratio: Li / (Ni+Co+Mn)=1.2:1; and ball-milled at a speed of 400 r / min for 2 h to obtain a mixed powder.

[0175] Example 4

[0176] Based on the positive electrode material B prepared in Example 3, a lithium ion button half-cell B was prepared.

[0177] Comparative Example 1

[0178] In this comparative example, a comparative positive electrode material C is prepared, and the preparation method includes P1 to P2.

[0179] P1: Lithium carbonate and manganese-based ternary hydroxide Ni 0.4 Co 0.05 Mn 0.55 (OH)2 was prepared according to the following molar ratio: Li / (Ni+Co+Mn)=1.2:1; and ball milled at a speed of 400r / min for 2h to obtain mixed powder C.

[0180] P2: The mixed powder C obtained in P1 was calcined at 650°C for 7h in an air atmosphere, cooled naturally, and then crushed and sieved to obtain a comparative positive electrode material C with W element doped on the surface.

[0181] Comparative Example 2

[0182] Based on the comparative positive electrode material C prepared in Comparative Example 1, a lithium ion button half-cell C was prepared.

[0183] Comparative Example 3

[0184] In this comparative example, a comparative positive electrode material D is prepared, and the preparation method includes Q1-Q2.

[0185] Q1: Lithium carbonate, tungsten trioxide and manganese-based ternary hydroxide Ni 0.4 Co 0.05 Mn 0.55 (OH)2 was configured according to the following molar ratio: Li / (Ni+Co+Mn)=1.2:1, W / (Ni+Co+Mn+W)=0.05:1; and ball milled at a speed of 400r / min for 2h to obtain mixed powder D.

[0186] Q2: The mixed powder D obtained in Q1 was calcined at 650°C for 7h in an air atmosphere, cooled naturally, and then crushed and sieved to obtain a comparative positive electrode material D with W element doped on the surface.

[0187] Comparative Example 4

[0188] Based on the comparative positive electrode material D prepared in Comparative Example 3, a lithium ion button half-cell D was prepared.

[0189] The lithium ion button half-cells prepared in the above-mentioned Example 2, Example 4, Comparative Example 2 and Comparative Example 4 were subjected to the first charge-discharge and rate cycle test. The test conditions are as follows: the first charge-discharge test was conducted at 0.1C / 0.1C at 25°C, and the discharge conditions were 0.1C, 0.33C, 0.5C, 1C, 2C, and 0.1C for 5 cycles respectively, and the voltage range was set to 2.0-4.6V. The test results are shown in FIG. Figure 3 and Figure 4 shown.

[0190] Depend on Figure 3 and Figure 4 It can be seen that, compared with Comparative Examples 2 and 4, under high voltage conditions, the first charge and discharge specific capacity, first coulomb efficiency and rate cycle test results of the lithium-ion button half-cells in Examples 2 and 4 are significantly improved. The main reason is that the composite coating material (LiV3O8-MWCNTs) makes the lithium-rich manganese-based positive electrode material have better electrochemical properties. Because the layered structure of LiV3O8 has a lithium embedding structure, it can provide more space for storing lithium ions, reducing Li +Irreversible embedding and de-embedding, while MWCNTs have excellent electronic conductivity, and the larger interlayer spacing in the structure can provide an effective channel for lithium ion embedding / ejection, and the cylindrical structure will not collapse after multiple charge and discharge cycles. The composite of LiV3O8 and MWCNTs can reduce the charge transfer impedance of lithium ions between material particles, which is beneficial to the efficient shuttling of Li+, thereby improving the electrochemical properties of the battery cell such as the first coulombic efficiency, cycle stability, and rate.

[0191] Moreover, compared with Example 4, the first charge and discharge specific capacity, first coulomb efficiency and rate cycle test results of the lithium-ion button half-cell in Example 2 are significantly improved. The main reason is that the introduction of the W element can improve the overall structural stability and thermal stability of the lithium-rich manganese-based positive electrode material, because it has a strong bonding force with oxygen, which can improve the stability of the material crystal structure, and the high-valent W element ions can induce the low-valent Ni 2+ The production of rock salt or spinel structure on the surface can inhibit oxygen release and phase transition, effectively reduce the occurrence of side reactions, and improve the cycle stability of the battery cell.

[0192] The above embodiments are only preferred embodiments for fully illustrating the present application, and the protection scope of the present application is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present application is within the protection scope of the present application.

Claims

1. A positive electrode material, characterized in that: include: Core material; The core material includes a lithium-rich manganese-based material; A composite coating material, coating the outer surface of the core material; The composite coating material includes a first material and a second material, wherein the first material includes carbon elements and forms a three-dimensional network structure with a cavity; the second material includes a portion located on the outer surface of the three-dimensional network structure and also includes a portion located in the cavity of the three-dimensional network structure; the second material is at least used to realize a lithium storage function.

2. The positive electrode material according to claim 1, characterized in that The first material includes at least one of carbon nanotubes, graphene and porous carbon.

3. The positive electrode material according to claim 2, characterized in that The first material includes multi-walled carbon nanotubes.

4. The positive electrode material according to claim 1, characterized in that The second material includes lithium vanadate.

5. The positive electrode material according to claim 1, characterized in that The thickness of the composite coating material ranges from 15nm to 30nm.

6. The positive electrode material according to claim 1, characterized in that In the composite coating material, the mass ratio of the first material to the second material is in the range of (0.02-0.03):

1.

7. The positive electrode material according to any one of claims 1 to 6, characterized in that The core material includes: a core material and a doping material, wherein the doping material covers the core material; the doping material includes: a lithium-rich manganese-based material containing tungsten ions.

8. The positive electrode material according to claim 7, characterized in that The atomic percentage of the tungsten ions in the core material is in the range of 2% to 3%.

9. The positive electrode material according to claims 1 to 6, characterized in that: The core material further comprises nickel and cobalt; the atomic percentage of nickel in the core material is less than the atomic percentage of manganese in the core material, and greater than the atomic percentage of cobalt in the core material.

10. A method for preparing a positive electrode material, characterized in that: include: forming a core material, wherein the core material comprises a lithium-rich manganese-based material; forming a composite coating material, and coating the composite coating material on the outer surface of the core material; The composite coating material includes a first material and a second material, wherein the first material includes carbon elements and forms a three-dimensional network structure with a cavity; the second material includes a portion located on the outer surface of the three-dimensional network structure and also includes a portion located in the cavity of the three-dimensional network structure; the second material is at least used to realize a lithium storage function.

11. The method for preparing the positive electrode material according to claim 10, characterized in that: The core material is formed, comprising: mixing a first lithium source, a manganese source and a tungsten source to obtain a mixed powder; The mixed powder is calcined to obtain the core material.

12. The method for preparing the positive electrode material according to claim 11, characterized in that: The manganese source is selected from any one of the following general formulas as shown in the structure: Ni b Co c Mn 1-b-c (OH)2; where 0≤c≤0.05, 0 <b≤0.4。 13. The method for preparing the positive electrode material according to claim 11, characterized in that: The first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; and / or, The tungsten source includes at least one of tungsten trioxide, tungsten sulfide and tungsten carbide.

14. The method for preparing the positive electrode material according to claim 11, characterized in that: The calcination temperature of the mixed powder is in the range of 600° C. to 800° C.; and / or, The calcination time of the mixed powder is in the range of 6 hours to 8 hours.

15. The method for preparing a positive electrode material according to any one of claims 10 to 14, characterized in that: The second material includes lithium vanadate, and a reaction for forming the second material is a solvothermal reaction.

16. The method for preparing the positive electrode material according to claim 15, characterized in that: The reaction temperature of the solvothermal reaction to form the second material is in the range of 60°C to 80°C.

17. The method for preparing the positive electrode material according to claim 15, characterized in that: The forming of the composite coating material and coating the composite coating material on the outer surface of the core material comprises: The vanadium source and the second lithium source are subjected to the first stage of the solvothermal reaction to obtain a first solution; wherein the configuration ratio of vanadium in the vanadium source to lithium in the second lithium source is 3:1, and the first solution includes lithium vanadate; adding a carbon source to the first solution, performing the second stage of the solvothermal reaction, and obtaining a second solution; adding the core material to the second solution to carry out the third stage of the solvothermal reaction to obtain a first precipitate; The first precipitate is calcined to obtain the positive electrode material.

18. The method for preparing the positive electrode material according to claim 17, characterized in that: The reaction time of the first stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction; and / or, The reaction time of the third stage of the solvothermal reaction is greater than or equal to the reaction time of the second stage of the solvothermal reaction.

19. The method for preparing the positive electrode material according to claim 18, characterized in that: The reaction time of the first stage of the solvothermal reaction is in the range of 1 h to 2 h; and / or, The reaction time of the second stage of the solvothermal reaction is in the range of 0.2h to 1h; and / or, The reaction time of the third stage of the solvothermal reaction ranges from 1 h to 2 h.

20. The method for preparing the positive electrode material according to claim 17, characterized in that: The carbon source includes at least one of carbon nanotubes, graphene and porous carbon.

21. The method for preparing a positive electrode material according to claim 17, characterized in that: The carbon source includes acid-treated multi-walled carbon nanotubes.

22. The method for preparing a positive electrode material according to claim 21, characterized in that: The carbon source is multi-walled carbon nanotubes treated with concentrated sulfuric acid and / or concentrated nitric acid; the acid treatment process is ultrasonic treatment; and the acid treatment time ranges from 2h to 4h.

23. The method for preparing the positive electrode material according to claim 17, characterized in that: The vanadium source comprises ammonium vanadate; and / or the second lithium source comprises lithium hydroxide monohydrate.

24. The method for preparing the positive electrode material according to claim 17, characterized in that: The calcination temperature of the first precipitate is in the range of 350°C to 400°C; and / or, The calcination time of the first precipitate is in the range of 10 h to 12 h.

25. A lithium ion battery, characterized in that: The invention comprises the positive electrode material as claimed in any one of claims 1 to 9 or the positive electrode material prepared by the preparation method as claimed in any one of claims 10 to 24.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material and preparation method thereof

    CN106532018A

  • A preparation method of lithium vanadate coated lithium-rich oxide solid solution material

    CN109103423A

  • Lithium-rich manganese-based layered positive electrode material as well as preparation method and application thereof

    CN116364907A

  • Doped and coated ternary positive electrode material as well as preparation method and application thereof

    CN116960310A